The emerging role of vascular endothelial cell-mediated angiogenesis in the imbalance of RA synovial microenvironment and its clinical relevance - Huo, Xingxing; Peng, Yanhui; Li, Hui; Li, Chen; Liao, Faxue; Miao, Chenggui; Huang, Yurong (Frontiers in Pharmacology, 2025)
Vascular endothelial cells (VEC) play a key role in the occurrence and progression of vascular inflammation. VEC activation secretes powerful inflammatory mediators and aggravates the development of rheumatoid arthritis (RA). Angiogenesis plays a key role in the pathological processes of inflammation and synovial infiltration, driving RA progression. A substantial amount of evidence suggests that the VEC at the inflammatory site of RA is both an active participant and a regulator of the inflammatory process. At present, the research progress of VEC and inflammation in RA is still incomplete. In this review, we summarize the role of VEC and angiogenesis in the development of RA, describe the relevant cells, cytokines and signaling pathways involved in regulation, and provide research clues on the role of post-translational modification (PTMs) in VEC function and angiogenesis in RA, and classify and integrate these mechanisms and therapeutic strategies. This review aims to synthesize current evidence to support the established link between VEC and RA-related pathology, provide a theoretical basis for clinical studies, and provide valuable insights into the development of therapeutic drugs against RA.